Lucas and Hume on Monetary Non-Neutrality: A Tension between the Logic and the Technique of Economics - Simon Bilo (Duke University, Center for the History of Political Economy (CHOPE), 2015)
Translation of old economic doctrines into new technical frameworks led the profession to lose a valid theory of monetary non-neutrality. The theory relates to how additional money diffuses through the economy after entering at different points. Diffusion takes time, redistributes resources, and changes relative prices. This theory of the non-neutrality of money was introduced into economics by David Hume, among others, but it has since disappeared from the leading conversations on monetary non-neutrality. However, the disappearance was not caused by any theoretical or empirical weakness. Using Lucas's Nobel lecture as my point of departure, I argue that it disappeared because it did not fit into the popular technical frameworks.
Keywords: 330; non-neutrality of money; Robert Lucas; David Hume